Normal pregnancy is associated with an increase in thrombin generation from the very early stages of the first trimester. Issue 157 (September 2017) - Bagot, C.N.; Leishman, E.; Onyiaodike, C.C.; Jordan, F.; Freeman, D.J.
Abstract: Background: Pregnancy is a hypercoagulable state associated with an increased risk of venous thrombosis, which begins during the first trimester, but the exact time of onset is unknown. Thrombin generation, a laboratory marker of thrombosis risk, increases during normal pregnancy but it is unclear exactly how early this increase occurs. Methods: We assessed thrombin generation by Calibrated Automated Thrombography in women undergoing natural cycle in vitro fertilization, who subsequently gave birth at term following a normal pregnancy ( n = 22). Blood samples were taken just prior to conception and repeated five times during very early pregnancy, up to Day 59 estimated gestation. Results: Mean Endogenous Thrombin Potential (ETP), peak thrombin generation and Velocity Index (VI) increased significantly from pre-pregnancy to Day 43 gestation ( p = 0.024–0.0004). This change persisted to Day 59 gestation. The mean of the percentage change from baseline, accounting for inter-individual variation, in ETP, peak thrombin and VI increased significantly from pre-pregnancy to Day 32 gestation ( p = 0.0351–<0.0001) with the mean increase from baseline persisting to Day 59 gestation. Conclusion: Thrombin generation increases significantly during the very early stages of normal pregnancy when compared to the pre-pregnancy state. The increased risk of venous thrombosis therefore likely begins very early in a woman's pregnancy, suggesting that women considered clinically to be at high thrombotic risk should start thromboprophylaxis as early as possible after a positive pregnancy test. Highlights: It is unclear how early in pregnancy women become hypercoagulable. The current study measured thrombin generation in women just before and during early pregnancy. Thrombin generation begins to increase during the fifth week of pregnancy. Pregnant women at increased risk of thrombosis should start thromboprophylaxis very early in pregnancy.